Willingness to pay for fast-track tickets in the alpine skiing industry: a case study of a Norwegian ski resort - Per Kristian Alnes; Gudbrand Lien; Erik Haugom; Iveta Malasevska; Ørjan Mydland (Cogent Social Sciences, 2024)
We evaluate a fast-track ticket alternative in the alpine skiing industry using data from a survey of skiers at a major ski resort in Norway. We estimate price-response functions, optimal prices for fast-track tickets and use regression to analyse the most important characteristics of skiers who demand the fast-track ticket alternative. Our findings show that the additional willingness to pay for a fast-track ticket over the standard day-pass ticket ranges from 4% (one minute waiting time) to 13% (20 minutes waiting time). The skiers with the highest demand for the fast-track ticket alternative are typically single men living near the ski resort who do most of their alpine skiing during the weekend. Some respondents expressed critical concerns regarding the fast-track ticket alternative, and we therefore discuss some customer acceptance challenges and ethical aspects associated with such an alternative.